2016
DOI: 10.1007/s10047-016-0925-6
|View full text |Cite
|
Sign up to set email alerts
|

Strict blood glucose control by an artificial endocrine pancreas during hepatectomy may prevent postoperative acute kidney injury

Abstract: The aim of the present study was to evaluate the usefulness of a closed-loop system (STG-55; Nikkiso, Tokyo, Japan), a type of artificial endocrine pancreas for the continuous monitoring and control of intraoperative blood glucose, for preventing postoperative acute kidney injury (AKI) in patients undergoing hepatectomy. Thirty-eight patients were enrolled in this study. Glucose concentrations were controlled with either a manual injection of insulin based on a commonly used sliding scale (manual insulin group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Previous studies have reported that glucose variability was associated with acute kidney injury following OLT [24,27,28] which was not related directly to hyperglycemia or hypoglycemia. However, this study did not detect a difference in the requirement for dialysis postoperatively between groups but we did not measure glucose variability.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have reported that glucose variability was associated with acute kidney injury following OLT [24,27,28] which was not related directly to hyperglycemia or hypoglycemia. However, this study did not detect a difference in the requirement for dialysis postoperatively between groups but we did not measure glucose variability.…”
Section: Discussionmentioning
confidence: 81%
“…These maneuvers generate glucose peaks due to the transition of the glycogen decomposition within hepatocytes secondary hypoxia that occurs in each pringle. [3][4][5] In addition to this, due to insulin resistance induced by liver disease per se, glucose metabolism is aggravated by hepatectomy and is not reversed during the intraoperative neohepatic stage; functional liver function then plays a decisive role in the metabolism of glucose. 6 In this case, the patient had a history of diabetes mellitus, requiring a more efficient control of glycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Blood was continuously sampled, and glucose levels were measured with a glucose sensor electrode and glucose oxidase membrane every minute. The pump delivering insulin and the glucose sensor electrode each had an accuracy of ±5% according to a previous report. We evaluated changes in insulin requirements from 00.00 to 08.00 hours as the “dawn phenomenon” using this artificial pancreas.…”
Section: Methodsmentioning
confidence: 99%